Drug release of pH/temperature-responsive calcium alginate/poly(N-isopropylacrylamide) semi IPN beads - Shi, Jun (2006)
A series of semi-interpenetrating, polymer network (semi-IPN), hydrogel beads, composed of calcium alginate (Ca-alginate) and poly(N-isopropylacrylamide) (PNIPAAM), were prepared for a pH/temperature-sensitive drug delivery study. The equilibrium swelling showed the independent pH- and thermo- responsive nature of the developed materials. At pH¼2.1, the release amount of indomethacin incorporated into these beads was about 10% within 400 min, while this value approached to 95% at pH¼7.4. The release rate of the drug was higher at 37 8Cthan that at 25 8C and increased slightly with increasing PNIPAAM content. These results suggest that the Caalginate/ PNIPAAM beads have the potential to be used as an effective pH/temperature sustainable delivery system of bioactive agents.